Dominica : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The Growth and Social Protection Strategy (GSPS) provides the framework for Dominica's economic and social policies over the next five years and sets out the macroeconomic framework; the growth strategy, including the enabling environment for private enterprise and sectoral strategies; and poverty reduction and social protection programs. Economic growth in Dominica was curtailed by a conjuncture of unfavorable developments, particularly with respect to trade, but there were underlying weaknesses in the economy such as a reliance on one or two sectors, with this lack of diversity exacerbating its vulnerability to economic shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet